Trends characterizing technological innovations that increase environmental pressure: A typology to support action for sustainable consumption - Lefèvre, Thierry; Déméné, Claudia; Arpin, Marie-Luc; Elzein, Hassana; Genois-Lefrançois, Philippe; Morin, Jean-François; Cheriet, Mohamed (Frontiers in Sustainability, 2022)
Technological innovation is widely recognized as an endogenous element of capitalism driving economic growth and consumption. Although technological innovations have benefited human health, quality of life and comfort, especially in high-income countries, uncontrolled industrialization of technological innovations and mass consumption exert strong environmental pressure on natural resources and contribute to the degradation of the environment. Apart from their endogenous role on economy and consumption, technological innovations are characterized by specific trends that affect the sustainability of manufactured goods and consumption patterns, such as rate of market penetration, product ownership, lifespan, reparability, and recyclability. As these different trends are often treated separately and mainly in the fields of electronics, we argue that a global view is needed in order to mitigate overconsumption patterns. This paper thus contributes to a better understanding of the impact of technological innovations on consumption in industrialized countries. Based on a review of the extant literature, the following typology of trends characterizing technological innovations is built: 1) accumulation; 2) diversification; 3) substitution; 4) complexification. After contextualizing the rate of penetration of technological innovations and its main drivers, we show how the four technological trends are interdependent, rooted in a historical perspective, and impact the socioeconomic metabolism. This altogether indicates that strong action in terms of sufficiency and technology assessment needs to be taken at the political level to undermine these trends and, more generally, the negative impacts emerging at the economy-technology-consumption nexus.